Integrating Instagram As A Media In Engaging Students Learn To Write Recount Text - Nina Puspitaloka; Yana Cahyana; Sandra Intan Sari (Universitas Persada Indonesia YAI, 2022)
This study discusses how Instagram is used as media in engaging students to learn to writerecount text. This study aims to look at how student engagement and students’ perspectiveson the use of Instagram as media in learning to write recount text. The use of Instagram asmedia in learning to write recount texts is considered as a communicative and flexiblemedia. Thus, it can be used to study inside the classroom and outside the classroom. Thisresearch design belongs to Classroom research by involving six undergraduate students.Student engagement are obtained through several instruments such as: observation sheets,interview guides, and documentation. The procedure of this research consists of Pre-Lesson, While-Lesson, and Post-Lesson. Data that has been obtained from some of theseinstruments is analyzed using the Miles and Huberman Method. The results of this studyillustrate that there are two phases of Instagram that assist students learn to write, they arethe photo selection phase and the caption writing phase where Instagram can stimulatestudent writing ideas and write them on the photo caption page. In addition, studentsrespond well when using Instagram as a learning medium for writing because they aremotivated to write well